Efficacy of moclobemide in burning mouth syndrome: a nonrandomized, open-label study - (:unkn) unknown (My University, 2008)
AIMS: To compare burning mouth syndrome (BMS) patients with age- and gender-matched controls for psychologic conditions, to analyze the effect of menstrual state on the intensity of burning, and to assess the efficacy of an antidepressant medication on the burning pain and psychologic status. METHODS: Ninety-four patients with BMS and 94 matched control subjects participated in the study. Anxiety and depression were analyzed by means of the Spielberger State-Trait Anxiety Inventory and Zung Self-Rating Depression Scale, and the severity of the burning sensation was measured by means of a visual analog scale (VAS). In female BMS patients and controls, the menstrual state was noted (menstruating, menopausal, or postmenopausal). BMS patients were treated with the antidepressant moclobemide (150 mg 2 times daily) for 3 months. Thereafter, anxiety, depression, and burning pain intensity were reassessed. Patient-perceived satisfactory improvement for burning sensation was assessed using a 5-point categorical rating of change scale. RESULTS: BMS patients had significantly higher anxiety and depression scores than controls (P < .05). After treatment, anxiety and depression scores as well as the VAS values for burning pain decreased significantly (P < .001). Thirty-seven patients reported good to very good improvement, and 44 reported satisfactory improvement. No adverse reactions were reported. CONCLUSIONS: The study confirmed earlier reports that BMS patients have higher anxiety and depression levels than controls. An antidepressant medication may be effective in alleviating the burning pain, at least in the short-term.
Keywords: Female; Humans; Male; Anxiety; Case-Control Studies; Analysis of Variance; Depression; Antidepressive Agents; Menstruation; Burning Mouth Syndrome; Moclobemide